Research on Decarbonization Pathway of China’s Coal-Fired Power Industry From the Perspective of Conflict Mediation - Fang, Yinhai; Xu, Haiyan (Frontiers in Environmental Science, 2022)
The transition to a low-carbon energy system is imminent under the constraints of carbon-peaking and carbon-neutral targets. Undoubtedly, the coal-related carbon emissions over the past decades have had profound negative impacts on human life and global climate. However, the main position of coal in the energy system determines that pure coal reduction strategy will inevitably lead to an energy systemic crisis. However, the main position of coal in the energy system determines that a coal-only emission reduction strategy will induce a systemic energy crisis. To this end, we explore the conflict formation mechanism among coal enterprises, downstream coal-fired power plants and government in the process of strategic energy decarbonization transformation from the perspective of industrial chain, and analyzes the feasible conflict states and their NASH, GMR, SMR and SEQ equilibrium characteristics by constructing a ternary GMCR model. It is found that there are two feasible conflict states s10 and s12 that simultaneously satisfy the conditions of the above four types of equilibria. In this context, the evolution paths of s10 and s12 are further analyzed and conflict mediation strategies are proposed accordingly. Meanwhile, the decarbonization transition of the energy system needs to consider both the stage characteristics and regional differences of energy reform, as well as the important role of green low-carbon technological innovation as a grip for the decarbonization transition of energy.